Moral Responsibility of Bystander Role in The Midst of Bullying: A Gender-Based Cross-Sectional Survey - Nuha, Moch. Syihabudin; Muslihati, Muslihati; Rahman, Diniy Hidayatur (International Journal of Education and Teaching Zone, 2025)
The bystander effect is the tendency of individuals to not respond to emergencies by helping, defending, or stopping them. Bullying is a sign that someone is in real and imminent danger. Efforts to involve bystanders in intervention will determine whether bullying becomes more severe or even does not occur if they have a moral involvement to their surroundings. This study will highlight the role of bystanders in bullying incidents, whether there is a correlation between the role of bystanders and gender, and how bystanders view bullying from a moral perspective. The research method uses a descriptive quantitative research design that will describe and explain the role of bystanders in bullying incidents. The research data was collected from 104 students aged 12-15 years with instrument bystander bullying role scale 37 items. This scale consists of bystander roles like defender, assistant, outsider, aggressive defender, and reinforcer. The assistant and reinforcer roles showed pro-bullying with findings of 5% and 42% in the moderate category. The defender and aggressive defender roles showed anti-bullying with findings of 22% and 56% in the moderate category. Meanwhile, the outsider role, which is the core of passive bystanders, was found to be 49% in the moderate category and 27% in the high category. The r value obtained was 0.036 < 0.195, indicating a weak correlation between bystander roles and gender. The various observer roles in both genders show that the bystander role can be performed by anyone and that there are individual characteristics that inhibit, reinforce, or are indifferent to bullying incidents. From a moral point of view, these findings show that it is important to develop a sense of moral responsibility and encourage bystanders to intervene on behalf of bullying victims, especially in the role of outsiders.